JAEPL, Vol. 23, Winter 2017-2018 - Joonna Smitherman Trapp; Brad Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
Editors’ Parting Message Essays The Politics of Consciousness, Kurt Spellmeyer Writing, Silence, and Well-being, Robert P. Yagelski Writing as a Liberal Art in an Age Neither Artful nor Liberal, Douglas Hesse The Tyranny of ‘Best Practices,’ Roger Thompson SPECIAL SECTION: TEACHING AND LEARNING AS BODILY ARTS Corporal Pedagogies: An Introduction, Wendy Ryden Embodied Databases: Attending to Research ‘Places’ through Emotion and Movement, Kati Fargo Ahern Embodied Ethos and a Pedagogy of Presence: Reflections from a Writing Yogi, Christy I. Wenger Rhetorics of Reflection: Revisiting Listening Rhetoric through Mindfulness, Empathy, and Non-Violent Communication, Renea Frey Performance and the Possible: Embodiment, Privilege, and the Politics of Teaching Writing, Lesley Erin Bartlett Un/learning Habituation of Body-Mind Binary through the Teaching/Learning Body/Mind, Jeong-eun Rhee, Stephanie L. Curley, and Sharon Subreenduth Book Reviews Looking for Solace, Irene Papoulis Golub, Adam, and Heather Richardson Hayton, eds. Monsters in the Classroom: Essays on Teaching What Scares Us. Jefferson, NC: McFarland and Company, Inc., 2017, Wendy Ryden Waite, Stacey. Teaching Queer: Radical Possibilities for Writing and Knowledge. Pittsburgh, PA: U of PA Press, 2017, Mark McBeth Eodice, Michele, Anne Ellen Geller, and Neal Lerner. The Meaningful Writing Project: Learning, Teaching, and Writing in Higher Education. Boulder, CO: Utah State UP, 2016, Mary Pigliacelli Connecting The Emotional Labor of Our Work, Christy I. Wenger Interdisciplinary Dangers: A Small Caveat, W. Keith Duffy One Mindful Step, Sheila M. Kennedy and Jen Consilio The Way to the Falls, Carl Vandermeulen A Good Rain, Robert Randolph